Carbon Sink Strength of Subsurface Horizons in Brazilian Oxisols. Issue 1 (4th January 2018) - Souza, Ivan F.; Almeida, Luis F. J.; Jesus, Guilherme L.; Pett-Ridge, Jennifer; Nico, Peter S.; Kleber, Markus; Silva, Ivo R.
Abstract : Core Ideas: Mineralogy cannot explain the formation of MOAs in topsoil. SRO and crystalline Al‐/Fe‐(hydr)oxides are both effective in the formation of MOAs in subsoil. The initial amount of C associated to Al‐/Fe‐(hydr)oxides seems to affect the formation of MOAs. Redistribution of plant litter towards the subsoil can enhance C storage in Oxisols. Interactions with pedogenic oxides are a known mechanism of soil organic matter (SOM) protection, but little is known about how the protective power of pedogenic oxides varies with soil depth in highly weathered tropical soils. To address this issue, we followed the decomposition of a double‐labeled plant litter ( 13 C/ 15 N) in microcosm experiments using samples collected at four depths (0–10, 10–20, 20–40, and 60–100 cm) from six Brazilian Oxisols. These soils were selected to include a range of taxonomic subtypes, spanning wide variations in mineralogy and texture. After a 12‐mo incubation, we quantified the proportion of isotopically‐labeled SOM ( 13 C/ 15 N) within the mineral fraction <53 µm (i.e., clay+silt). We found that litter‐C retention increased with depth, while the opposite occurred for litter‐N. Correlations between isotopically‐labeled SOM and short‐range order (SRO) Al‐/Fe‐(hydr)oxides were insignificant in topsoil (0–10 cm), but increased with depth, reaching peak significance in the 20‐ to 40‐cm interval ( r = 0.64 and 0.58, for litter‐C and ‐N, respectively). A similar trend was observed for crystalline Al‐/Fe‐(hydr)oxides, which were more strongly correlated with the retention of 13 C than 15 N. We posit that in subsoil, both SRO and crystalline Al‐/Fe‐(hydr)oxides are more readily involved in the neoformation of mineral‐organic associations. Overall, litter‐C is less efficiently transferred into the clay+silt fraction of C‐rich topsoil relative to C‐depleted subsoil horizons, which may represent a significant C sink for Oxisols.